2019
DOI: 10.1002/ente.201800961
|View full text |Cite
|
Sign up to set email alerts
|

Carbon–Silica Composite as an Effective Support for Iron Fischer–Tropsch Synthesis Catalysts

Abstract: Carbon–silica composite is prepared by the impregnation of silica with aqueous glucose solution followed by drying and calcination in an inert atmosphere. This material is proposed as a support for the potassium‐promoted iron catalysts for Fischer–Tropsch synthesis (FTS). The catalysts are prepared by incipient wetness impregnation. The reducibility of CQ‐supported iron is increased and Hägg carbide is formed in the course of activation in CO/H2 flow at 400 °C for 2 h. Subsequent exposure in FTS conditions res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 50 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…They [15] ascribed this to the presence of defects in magnetite, which lower the activation energy from 88 to 39 kJ/mol when it is being reduced to iron. Chenavskii et al's [96] observation shows that under syngas reduction, Hägg carbide is formed at 400 °C. A study carried out by Li et al [97] to determine the effect of reducing agents on iron-based MOF catalysts for use in FTS, revealed that using iron catalysts reduced in H 2 resulted in the formation of elemental iron, while Fe 3 C was produced from syngas, and a large portion of Fe 3 O 4 was obtained from H 2 reduction.…”
Section: Active Phases Of Iron-based Catalysts In Ftsmentioning
confidence: 99%
See 2 more Smart Citations
“…They [15] ascribed this to the presence of defects in magnetite, which lower the activation energy from 88 to 39 kJ/mol when it is being reduced to iron. Chenavskii et al's [96] observation shows that under syngas reduction, Hägg carbide is formed at 400 °C. A study carried out by Li et al [97] to determine the effect of reducing agents on iron-based MOF catalysts for use in FTS, revealed that using iron catalysts reduced in H 2 resulted in the formation of elemental iron, while Fe 3 C was produced from syngas, and a large portion of Fe 3 O 4 was obtained from H 2 reduction.…”
Section: Active Phases Of Iron-based Catalysts In Ftsmentioning
confidence: 99%
“…Chenavskii et al [96] showed that potassium promoters affect the reducibility and carburization behaviour of iron. From their previous work [96], it was concluded that potassium aids in the formation of iron carbides.…”
Section: The Role Of Promoters On Iron-based Catalysts During Auto-re...mentioning
confidence: 99%
See 1 more Smart Citation
“…Two other studies from 2019 utilizing this new version of the earthicle focused on the analysis of the pros and cons of distributing the particles to the cells as powders or as colloidally stable ferrofluids 321 and on the ability of the ferrofluids to act as a material for targeted magnetic separation of cancer cells, bacteria, and specific types of biomolecules. 322 Furthermore, while the doubly shelled iron (oxide) particles conforming to the composition of the earthicle are yet to be studied thoroughly for their catalytic properties, a study from 2019, demonstrating a beneficial effect of carbon−silica composite support on the catalytic activity of iron in CO hydrogenation of the Fischer−Tropsch type while suppressing the formation of methane and increasing Anderson−Schulz− Flory distribution chain growth parameter, 323 hints at the immense potential of these materials for such applications. Another hint at things that are yet to come comes from another study from 2019, in which case a composite formed by embedding metallic iron particles inside a silica matrix and subsequently carbonizing the latter exhibited an excellent cyclic stability and rate capability, enhanced diffusion coefficient for lithium ions, and low transfer resistance when tested as a potential anode for lithium-ion batteries.…”
Section: Triphasic Compositions Comprising Iron (Oxides) Silica and C...mentioning
confidence: 99%
“…Then iron and optionally potassium as an electronic promoter are introduced by incipient wetness impregnation (IWI). [ 28 ]…”
Section: Introductionmentioning
confidence: 99%